2016
DOI: 10.1063/1.4942783
|View full text |Cite|
|
Sign up to set email alerts
|

A practical biogas based energy neutral home system for rural communities of Bangladesh

Abstract: Growing demand of energy consumption, subsequent increase in energy generation costs, and increased greenhouse gas (GHG) emissions, as well as global warming from the conventional energy sources, encourages interest worldwide to bring a higher percentage of renewable energy sources such as biogas into the energy mix to build a climate friendly environment for the future. Moreover, due to high investment and maintenance costs, governments are not providing enough support for grid extension and delivering electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…They can be divided into two categories: the use of biogas in households, for example, for cooking or heating ( n = 10), or in tractors or agricultural machinery ( n = 7). The biogas for use in households is normally produced in a decentralized manner and used directly, for example, for cooking (Hamid and Blanchard 2018 ), but also to supply power or produce fertilizer for agricultural purposes (Das et al 2016 ). Another goal of decentralized plants can be waste disposal, for example, of wastewater (Bensah and Brew-Hammond 2010 ) or to reduce greenhouse gas (GHG) emissions (Yuan et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be divided into two categories: the use of biogas in households, for example, for cooking or heating ( n = 10), or in tractors or agricultural machinery ( n = 7). The biogas for use in households is normally produced in a decentralized manner and used directly, for example, for cooking (Hamid and Blanchard 2018 ), but also to supply power or produce fertilizer for agricultural purposes (Das et al 2016 ). Another goal of decentralized plants can be waste disposal, for example, of wastewater (Bensah and Brew-Hammond 2010 ) or to reduce greenhouse gas (GHG) emissions (Yuan et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another goal of decentralized plants can be waste disposal, for example, of wastewater (Bensah and Brew-Hammond 2010 ) or to reduce greenhouse gas (GHG) emissions (Yuan et al 2015 ). Research interest in biogas plants for household use is concentrated in Africa (Kenya (Hamid and Blanchard 2018 ), Ghana (Bensah et al 2011 ; Bensah and Brew-Hammond 2010 ) and Africa in general (Kemausuor et al 2018 )), and Asia (Bangladesh (Das et al 2016 ), China (Chen et al 2012 ; Yuan et al 2015 ), Indonesia (Silaen et al 2020 ), Bali (Bößner et al 2019 ) and Pakistan (Yasmin and Grundmann 2019 )).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing uncertainty in energy flow in power grids today is due to intermittent production of renewable resources and time-varying load (Ashfaq and Ianakiev, 2018;Ludin et al, 2018;Liu et al, 2019;Peng et al, 2019;Sun et al, 2019). Therefore, power grids are facing a period of change caused by many issues such as reliability (Schienbein and DeSteese, 2002;Islam et al, 2015) and expansion of the power system (Carrano et al, 2007), power quality improvement (Short, 2018), load growth management (Das et al, 2013a;Hossain et al, 2015;Van Der Stelt et al, 2018;Mousavi et al, 2019), penetration of renewable resources (Das and Alam, 2012;Das et al, 2013b;Das et al, 2016;Yan et al, 2017), and minimization of greenhouse gas emission (Mazumder et al, 2014;Nemet et al, 2016). Incorporating battery energy storage (BES) in the distribution system is rapidly increasing to provide many benefits to environmental, technical, and economic issues (Das et al, 2018a;Das et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is found that combustible element is possible to increase by 54.38% if it is filtered in a particular way [25]. Setting the biogas plant in rural areas can solve the electricity crisis as well as the energy is usable in cooking and produce a good quality of fertilizer for agricultural purpose which is cost effective and less GHG emissions and help to improve the socio-economic conditions of the people [26].In rural areas of many developing countries are using firewood which is not only destroying the plants but also creating environmental problems and health hazards. So, it's very urgent to develop an alternative energy source that will address the problems and reduce the burden on fossil fuel.…”
Section: Introductionmentioning
confidence: 99%